1907 Tenn. Pub. Acts 208, ch. 74, § 2, pt. 11. - (:unkn) unknown (My University, 1907)
[T]o regulate the discharging, firing, shooting, or carrying of guns, pistols, and fireworks in the town; to regulate or prohibit the selling within the limits of the town fireworks of any kind whatever.
Keywords: DISCHARGE